BATUAN SEDIMEN HALUS KELOMPOK MANDAI BERDASARKAN ANALISIS SCANNING ELECTRON MICROSCOPE (SEM) - Zajuli, M.H. Hermiyanto (Pusat Survei Geologi, 2013)
The eastern part of the Ketungau basin that is generally known us the Mandai sub-basin is a sedimentary basin that had been formed since early Tertiary. Fine-grained sedimentary rocks taken from the Mandai Group comprising four samples of mudstone and three samples of siltstone. Based on Scanning Electron Microscope analysis seven samples fine sediment of the Mandai group consist of illite (K1-1.5Al4(Si7-6.5Al1-1.5O20)(OH)4, smectite (1/2Ca)0.7(Al,Mg,Fe)4(Si,Al)8O20)nH2O and kaolinite (Al4(Si4O10)(OH)8. Other minerals are silica or fine-grained quarzt, feldspar, and algae (botryococcus). Diagenesis processes show that fine sediment of the Mandai group have undergone a diagenetic process within an mesodiagenetic level. Fine sediments have been buried at more than 2500 - 4000 m depth by temperature varying from 80° to 120°C.Key words : Ketungau Basin, SEM, diagenesis, siltstone, mudstone